Analisis Tantangan Baru Nilai Publik dan Akuntabilitas di Era Digital - R. Neneng Rina Andriani; Dermawan, Wildan Dwi; Adil Ridlo Fadillah (Universitas Pamulang, 2025)
This study aims to investigate the development of publications on public value and accountability and find future prospects for the topic. Data were observed from Dimension AI database with the keywords